Factors influencing an increase in the U.S. study abroad poplulation in the Middle East/North Africa - Lane, Cara Kathleen (AUC Knowledge Fountain, 2011)
In the last 60 years, the relationship between the United States and the Middle East has become increasingly important to policy makers, academics, business people, and the general population. Particularly in the fallout of the events of September 11, 2001, both the U.S. government and the public have acknowledged an immediate need for a deepening of American understanding of the people, languages, and culture of the Middle East/North Africa (MENA). During the last decade, one significant way in which Americans have gained in-depth knowledge about this region has been through participation in Study Abroad (SA) programs. Data from the Institute for International Education show the number of U.S. undergraduate students studying abroad in the MENA is increasing, yet there is almost no literature related to SA in this region. The purpose of this study is to 1) characterize students who study in the Middle East/North Africa region and 2) assess the factors which cause some study abroad students to choose this less common region rather than a more common destination. In order to investigate the motivations, attitudes, and aspects of human capital which influence study abroad destination choice, this research examines seven main factors: exposure to international issues, attitudes about national security, career intentions, language exposure, previous international travel experience, risk propensity, and scholarship support. This research analyzes data from a cross-sectional survey and focus groups of current U.S. undergraduate study abroad students. Despite the large amount of research on outcomes and educational approaches used in SA in general, there is little literature which addresses influences on destination choice in SA. Given the increasing trend in SA programs in MENA region, this analysis provides insight into the multitude of factors which are leading students to this area of the world.